2016
DOI: 10.1038/ncomms13668
|View full text |Cite
|
Sign up to set email alerts
|

Truncation and constitutive activation of the androgen receptor by diverse genomic rearrangements in prostate cancer

Abstract: Molecularly targeted therapies for advanced prostate cancer include castration modalities that suppress ligand-dependent transcriptional activity of the androgen receptor (AR). However, persistent AR signalling undermines therapeutic efficacy and promotes progression to lethal castration-resistant prostate cancer (CRPC), even when patients are treated with potent second-generation AR-targeted therapies abiraterone and enzalutamide. Here we define diverse AR genomic structural rearrangements (AR-GSRs) as a clas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
160
1
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 147 publications
(174 citation statements)
references
References 52 publications
11
160
1
2
Order By: Relevance
“…Specific ARGSRs resulting in 'hard-wired' ligand independence have been observed in model systems, but only recently in patients (17,22). Although a prior study of 30 heavily pre-treated mCRPC patients suggested an association between detection of any AR-GSR and poor clinical response to AR-targeted therapy (22), the relevance for treatment-naive mCRPC patients remained unclear.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Specific ARGSRs resulting in 'hard-wired' ligand independence have been observed in model systems, but only recently in patients (17,22). Although a prior study of 30 heavily pre-treated mCRPC patients suggested an association between detection of any AR-GSR and poor clinical response to AR-targeted therapy (22), the relevance for treatment-naive mCRPC patients remained unclear.…”
Section: Discussionmentioning
confidence: 99%
“…AR gene truncations in ctDNA are associated with primary resistance Truncated AR variants with intact N-terminal domain and DNA binding domain (exons 1-3) can display ligand-independent activity (14). While truncation of the LBD can occur through alternative splicing of cryptic exons (15), AR genomic structural rearrangements (AR-GSRs) can also give rise to ligand-independent variants (16,17). To assess the relevance of AR-GSRs for first-line abiraterone or enzalutamide response, we applied a sequencing approach designed to capture AR introns in 50 patient samples with high ctDNA (median 43%, range 12% -89%) (Supplementary Figure S15).…”
Section: Specific Classes Of Genomic Alteration Are Independently Assmentioning
confidence: 99%
“…A recent study revealed a positive correlation between AR copy number increase and upregulation of LBD-deficient AR splice variants (AR-Vs) (41). The find-…”
Section: Steroid Receptor Splice Variantsmentioning
confidence: 94%
“…Acetylation is mediated by p300 histone acetyltransferase enzymes, which associate with the p160 family of NCOAs (NCOA1-3). Removal of acetyl groups from chromatin counteracts ings further suggested that AR genomic rearrangements enhance the production of AR-Vs in a subset of patients (41). AR-Vs can promote resistance by engaging AR chromatin-binding sites (42) and by driving AR-dependent transcription in a constitutive ligand-independent manner (43)(44)(45).…”
Section: Alterations In Collaborating Factorsmentioning
confidence: 99%
“…Whole exome and whole genome sequencing efforts on clinical castration-recurrent (CR) CaP specimens confirmed the presence of somatic alterations that contribute to AR re-activation in at least 60% of patients (Beltran, et al 2013; Grasso, et al 2012; Robinson, et al 2015). Targeted deep sequencing of the AR gene locus on metastatic CR-CaP samples obtained at rapid autopsy and on circulating tumor DNA from CR-CaP patient serum have isolated additional genomic structural alterations in the AR gene that give rise to androgen-independent AR forms in 30%-50% of patients (De Laere, et al 2017; Henzler, et al 2016). The latter findings indicate that the actual fraction of patients whose CR-CaP harbors AR alterations is likely even higher.…”
Section: Introductionmentioning
confidence: 99%